2017
DOI: 10.4102/sajpsychiatry.v23i0.1054
|View full text |Cite
|
Sign up to set email alerts
|

Accountable or not accountable: A profile comparison of alleged offenders referred to the Free State Psychiatric Complex Forensic Observation Ward in Bloemfontein from 2009 to 2012

Abstract: BackgroundThe crime rate in South Africa is extraordinarily high. The problem of crime is further complicated when a person, who suffers from a mental illness, becomes involved in a crime. Furthermore, the forensic evaluation of a person suspected of having a mental illness involved in alleged criminal behaviour can be challenging. However, a dearth of information exists in South African literature regarding the link between crime and mental illness.AimTo determine the percentage of alleged offenders, referred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…The majority of suspected criminal offenders assessed in this study were male (95.65%), single, unemployed and had a lower level of education, which is similar to other local outpatient and inpatient studies. 9 , 10 , 11 , 16 The median age in this study was 29 years, similar to other studies; for example, Zapf et al’s study found a median age of 33 years, 17 Calitz et al of 30 years 16 and Marais et al of 32 years. 8 The demographic profiles seen on an outpatient basis appears to be in keeping with those observed on an inpatient basis in both local and international studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The majority of suspected criminal offenders assessed in this study were male (95.65%), single, unemployed and had a lower level of education, which is similar to other local outpatient and inpatient studies. 9 , 10 , 11 , 16 The median age in this study was 29 years, similar to other studies; for example, Zapf et al’s study found a median age of 33 years, 17 Calitz et al of 30 years 16 and Marais et al of 32 years. 8 The demographic profiles seen on an outpatient basis appears to be in keeping with those observed on an inpatient basis in both local and international studies.…”
Section: Discussionsupporting
confidence: 87%
“… 23 The assessment of these individuals must take into account the range of social, cognitive, behavioural and communicative characteristics of the assessee. 24 Studies in KZN found a higher prevalence of individuals with intellectual disability (22.7% in this study and 36.26% in the study by Houdi 10 ) compared with studies in other provinces (19% in the study by Ndala 11 and 20.1% in the study by Du Plessis 9 ). This indicates a gap in addressing the needs of this population in communities to prevent high levels of offending behaviour, as well as the proper diversion and rehabilitation of individuals with intellectual disability.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…42% fulfilled SCAN criteria for current depression disorder diagnosisLowBarrett et al 2007 [52]PrevalenceForensic wardSouth AfricaNCensusYes, No71, NS, 94.4%Psychiatric referralsNC *Detained “state patients” accused but found unfit to stand trial or not responsible, referred to forensic wardPsychiatric record (D)Schizophrenia (35.2%), mental retardation (22.5%) and psychoses other than schizophrenia (11.3%) most prevalent, followed by bipolar disorder (5.6%). 84.5% not able to stand trial and not accountable; 7% not fit to stand trial and accountable; 8.5% not accountable and fit to stand trialMediumBuchan 1976 [104]PrevalenceForensic wardZimbabweNCensusNo, No256, NS, NSPsychiatric referralsU *Referrals to hospitalPsychiatric record (D)Prevalence of schizophrenia 44%; epilepsy 22%HighCalitz et al 2006 [105]PrevalenceForensic wardSouth AfricaNCensusYes, No514, 30 (median), 94.6%Psychiatric referralsNC/A *Awaiting trial, referrals to hospitalPsychiatric record (D)46% psychiatric prevalence.Mediumdu Plessis et al 2017 [106]PrevalenceForensic wardSouth AfricaNCensusYes, No505, NA, 94%Awaiting trial; psychiatric referralsNC/A *Awaiting trial, referrals to hospitalPsychiatric record (D)Those not accountable significantly more likely to have mental illness (p = 0.0001) and be diagnosed with schizophrenia (p = 0.0001), intellectual disability (p = 0.0001), and substance-induced psychotic disorder (p = 0.02) than those not accountable. 98% of those found not accountable had mental illness.…”
Section: Methodsmentioning
confidence: 99%
“…18 , 19 Other published studies that have been previously conducted in South Africa on offenders referred by courts for psycho-legal evaluation under the CPA have either been confined to single sites, with relatively small sample sizes, or have focused primarily or exclusively on male offenders. 20 , 21 , 22 , 23 , 24 , 25 …”
Section: Introductionmentioning
confidence: 99%